Abandoned Buildings, Living Communities: Local Resistance to Preservation in Dawson City, Yukon - Burns, Jane (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1999)
Dawson City is many things to many people. To the local white community, Dawson City is a home where they live within both a tourist destination and a globally recognised historic site. Many resist these labels, quietly opposing the reconstruction and tourism movements that have dictated much of Dawson City’s community history since the 1960s. Although they admit, “We’re living off our history, ” residents resist the power which has been given to the federal agency, Parks Canada, to decide which buildings should be restored and which should be left to die a “natural death.”